If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(8x+3)=-4x+11
We move all terms to the left:
-3(8x+3)-(-4x+11)=0
We multiply parentheses
-24x-(-4x+11)-9=0
We get rid of parentheses
-24x+4x-11-9=0
We add all the numbers together, and all the variables
-20x-20=0
We move all terms containing x to the left, all other terms to the right
-20x=20
x=20/-20
x=-1
| 2(4c-1)-2=4c+4 | | 8c+5=4c−11 | | 7.6x+4+8.7x-1=140 | | 6X(-7)=5x+1 | | 2(h-60+20=-4 | | 2/3n-1=2/9n-4 | | 4+2(x-1)=8 | | 24.95x+.10=19.95x+20 | | x+24=x(x-4) | | 2p-12=-15 | | -4-3n/4=2 | | -2×-5y=-2 | | 4y-15y=2 | | -21=1/2c=18 | | 5(2X-3)=(x-2)+5 | | x/5+10=9 | | 17x+3+8x+2=54 | | 2x+10+3x+15=105 | | -3-2x+4=24 | | 3/5-6=1/10x+7 | | -5x+4(3+2x)=8x+12-3x | | 1-4r=4(1-r) | | 5(2X9,-3)=2(x-2)+5 | | -12+2n=-6 | | 5g+1=2g-5 | | X^2/3x=24/9 | | 18x-35x=2 | | 3x+7+3x+14=21 | | 100x=77.7 | | 10/4=40/n | | 4(2x+3)=12+8x | | 26/x*3.50=8.50 |